Mitochondrial Targeted Endonuclease III DNA Repair Enzyme Protects against Ventilator Induced Lung Injury in Mice - Masahiro Hashizume; Marc Mouner; Joshua M. Chouteau; Olena M. Gorodnya; Mykhaylo V. Ruchko; Glenn L. Wilson; Mark N. Gillespie; James C. Parker (MDPI AG, 2014)
The mitochondrial targeted DNA repair enzyme, 8-oxoguanine DNA glycosylase 1, was previously reported to protect against mitochondrial DNA (mtDNA) damage and ventilator induced lung injury (VILI). In the present study we determined whether mitochondrial targeted endonuclease III (EndoIII) which cleaves oxidized pyrimidines rather than purines from damaged DNA would also protect the lung. Minimal injury from 1 h ventilation at 40 cmH2O peak inflation pressure (PIP) was reversed by EndoIII pretreatment. Moderate lung injury due to ventilation for 2 h at 40 cmH2O PIP produced a 25-fold increase in total extravascular albumin space, a 60% increase in W/D weight ratio, and marked increases in MIP-2 and IL-6. Oxidative mtDNA damage and decreases in the total tissue glutathione (GSH) and the GSH/GSSH ratio also occurred. All of these indices of injury were attenuated by mitochondrial targeted EndoIII. Massive lung injury caused by 2 h ventilation at 50 cmH2O PIP was not attenuated by EndoIII pretreatment, but all untreated mice died prior to completing the two hour ventilation protocol, whereas all EndoIII-treated mice lived for the duration of ventilation. Thus, mitochondrial targeted DNA repair enzymes were protective against mild and moderate lung damage and they enhanced survival in the most severely injured group.